2014
DOI: 10.1074/jbc.m113.531467
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis Rates of Different Small Interfering RNAs (siRNAs) by the RNA Silencing Promoter Complex, C3PO, Determines Their Regulation by Phospholipase Cβ

Abstract: Background: PLC␤ reverses siRNA down-regulation possibly by binding to the RNA silencing promoter C3PO. Results: PLC␤ binds externally to C3PO to reduce rapid hydrolysis of specific siRNAs. Conclusion: A model for PLC␤ effects on C3PO-mediated siRNA hydrolysis is presented. Significance: The studies provide a clue of the genes that may be regulated by cytosolic PLC␤.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 29 publications
(43 reference statements)
2
30
0
Order By: Relevance
“…C3PO is an octamer consisting of 6 translin subunits that are responsible for the binding of specific oligonucleotides and 2 TRAX subunits that hydrolyze the bound oligonucleotides (7). We have found that PLCβ binds to an external site on one or both of the TRAX subunits in a 1:1 stoichiometric manner (13). Previously we observed that when we overexpressed TRAX in HEK293 cells that were overproducing both PLCβ1 and Gα q , we could quench the rise in intracellular Ca 2+ resulting from activation of Gα q ‐PLCβ (10).…”
Section: Resultsmentioning
confidence: 99%
“…C3PO is an octamer consisting of 6 translin subunits that are responsible for the binding of specific oligonucleotides and 2 TRAX subunits that hydrolyze the bound oligonucleotides (7). We have found that PLCβ binds to an external site on one or both of the TRAX subunits in a 1:1 stoichiometric manner (13). Previously we observed that when we overexpressed TRAX in HEK293 cells that were overproducing both PLCβ1 and Gα q , we could quench the rise in intracellular Ca 2+ resulting from activation of Gα q ‐PLCβ (10).…”
Section: Resultsmentioning
confidence: 99%
“…We attached a fluorescent probe / quencher pair to the ends of different siRNA molecules to monitor hydrolysis of different sequences by C3PO in real time. Our studies found that C3PO hydrolyzes siRNA (GAPDH) at a much faster rate than siRNA (Hsp90) (Sahu, Philip, 2014). However, when PLCβ is bound to C3PO, the hydrolysis rate for siRNA (GAPDH) is significantly reduced while the rate for siRNA (Hsp90) is unchanged (see Fig.…”
Section: Topicsmentioning
confidence: 81%
“…However, when PLCβ is bound to C3PO, the hydrolysis rate for siRNA (GAPDH) is significantly reduced while the rate for siRNA (Hsp90) is unchanged (see Fig. 5, from (Sahu, Philip, 2014)).…”
Section: Topicsmentioning
confidence: 99%
See 2 more Smart Citations